Orderan Fiktif Dalam Ekosistem Gig Economy: Analisis Status Hukum Ojek Online dan Perbandingan Hukum Indonesia-Inggris - Ummu Kholifah; Irma Mangar (Fakultas Hukum Universitas Islam Jember, 2025)
The development of digital technology has encouraged the birth of the gig economy that offers work flexibility through digital platforms such as online motorcycle taxis (ojol). However, the legal status of ojol drivers who are classified as partners, not workers, raises significant problems, especially related to the case of fictitious orders. This study aims to analyze the implications of the legal status of gig workers in Indonesia, especially ojol drivers, and to make a comparison with regulations in the UK. The research method used is normative-empirical law with a legislative, comparative law, and case approach. Primary data was obtained through interviews and observations of ojol drivers in Bojonegoro, while secondary data came from laws and regulations and court decisions. The results of the study showed that all respondents had experienced fictitious orders that caused economic and psychological losses, but did not receive legal protection due to their status as partners. The standard clause in the platform agreement shifts all responsibility to drivers, reflecting their weak bargaining position. Meanwhile, a comparison with the UK through the Uber BV v Aslam decision shows that drivers are categorized as workers who are entitled to basic protections such as minimum wage and paid leave